2021
DOI: 10.1128/jvi.00996-21
|View full text |Cite
|
Sign up to set email alerts
|

The Compound SBI-0090799 Inhibits Zika Virus Infection by Blocking De Novo Formation of the Membranous Replication Compartment

Abstract: Zika virus (ZIKV) is a mosquito-borne pathogen classified by the World Health Organization (WHO) as a public health emergency of international concern in 2016, and it is still identified as a priority disease. Although most infected individuals are asymptomatic or show mild symptoms, a risk of neurologic complications is associated with infection in adults. Additionally, infection during pregnancy is directly linked to microcephaly and other congenital malformations. Since there are no currently available vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…16,[75][76][77][78] Both mutagenesis and pharmacological approaches recently demonstrated that NS4A regulates the biogenesis of these replication factories. 12,17 Most notably, Riva and colleagues have shown that ZIKV NS4A function in replication organelle morphogenesis can be specifically inhibited by the compound SBI-0090799. 17 Moreover, NS4A inhibits the Akt-mTOR pathway and the growth of neurospheres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,[75][76][77][78] Both mutagenesis and pharmacological approaches recently demonstrated that NS4A regulates the biogenesis of these replication factories. 12,17 Most notably, Riva and colleagues have shown that ZIKV NS4A function in replication organelle morphogenesis can be specifically inhibited by the compound SBI-0090799. 17 Moreover, NS4A inhibits the Akt-mTOR pathway and the growth of neurospheres.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse genetics and pharmacological approaches recently demonstrated that NS4A of ZIKV and dengue virus (DENV, closely related to ZIKV) contribute to the biogenesis of ER-derived replication organelles which host the vRNA synthesis process. 12,17 In addition, the NS4A-NS4B precursor is also believed to play specific roles in flavivirus life cycle. 18 Interestingly, DENV NS4B is the target of a several highly potent antivirals, including two currently in phase 2 clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…To determine at which stage the drug displayed inhibitory efficiency, a time-of-addition assay was developed as previously described. 32 Vero cells were seeded in a 12-well plate overnight and infected with ZIKV at an MOI = 0.1. Then the culture medium was removed after 1 h of infection with ZIKV viral inoculum.…”
Section: Time Of Addition Assaymentioning
confidence: 99%
“…It has been noted that residues of the N-terminal region of NS4A are indispensable for NS4A stability. Point mutations of some conserved residues within this region affect membrane proliferation [101,110]. Such observed effects might be due to alterations in membrane binding after mutation.…”
Section: Dengue Ns4amentioning
confidence: 99%